STUDIES ON LEWIS ACID REACTION OF ISOEUGENOL AND ISOEUGENYL ACETATE - Bambang Purwono; Retno Dwi Soelistyowati; Mudasir Mudasir (Indonesian Journal of Chemistry, 2003)
Studies of the Lewis Acid (AlCl3 and BF3-methanol) to isoeugenol and isoeugenyl acetate have been conducted. Reactions were carried out by stirring of isoeugenol and isoeugenyl acetate for 4 days at room temperature.Structure analysis of the products using IR, MS, 1H NMR and 13C NMR spectrophotometer showed that cyclic dimer product has been obtained white crystal, 175 oC, as a 1-ethyl-5-hydroxy-3-(4-hydroxy-3-methyl phenyl)-6-methoxy-2-methyl indane.